Long-term safety of prenatal and neonatal exposure to paracetamol: a protocol for a systematic review. Issue 1 (7th December 2020) - Samiee-Zafarghandy, Samira; Sushko, Katelyn; Van Den Anker, John
Abstract : Introduction: A surge in the use of paracetamol in neonates has resulted in growing concerns about its potential long-term adverse events. In this study, we conduct a systematic review of the long-term safety of prenatal and neonatal exposure to paracetamol in newborn infants. Methods and analysis: We will follow the Joanna Briggs Institute Manual for Evidence Synthesis and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statements to conduct and report this review. We will conduct a systematic search of Embase, MEDLINE, Web of Science and Google Scholar for studies with data on long-term adverse events in neonates that were exposed to paracetamol in the prenatal and/or neonatal period. We will not apply language or design limitations. We will use standardised risk of bias assessment tools to perform a quality assessment of each included article. Ethics and dissemination: This systematic review will only involve access to publicly available data, and therefore ethical approval will not be required. The results of this study will be communicated to the target audience through peer-reviewed publication as well as other knowledge exchange platforms, such as conferences, congresses or symposia. Trial registration: The protocol for this systematic review is submitted for registration to international database of prospectively registered systematic reviews (PROSPERO, awaiting registration number).